The Issues of Improvement for the Institute of Claim Security in Administrative Procedure - Badalyan, Sayad (Bulletin of Yerevan University C: Jurisprudence, 2023)
The Code of Administrative Procedure (CAP) in the Republic of Armenia needs to improve its regulations for the institute of securing a claim. Chapter 15 of the CAP (Claim Security) has imperfect regulations that are not in line with current procedural legislation. Adjustments in Article 83 and Chapter 15 of the CAP could contribute to the improvement of the institute of securing a claim in administrative procedures. Article 83 of the CAP is one of the most discussed articles since it entered into force. It introduced the suspension of an administrative deed by force of law and not by the court, which poses inevitable risks, such as an opportunity for plaintiffs to abuse their rights. Overall, the issues with Article 83 and Chapter 15 of the CAP highlight the need for consistent adjustments and a systemic solution to the problem in order to improve the institute of securing a claim in administrative procedure. In this context, it is proposed that the general rule should not be the suspension of the administrative deed, and then the definition of exceptions to that rule, but Article 83 of the CAP should define only those cases when accepting a challenging claim suspends the performance of the administrative deed. However, it’s important to note that this does not imply that the execution of an administrative deed should never be suspended in cases not listed in Article 83 of the CAP. In such instances, the court may still order suspension as a means of securing the claim if there are pertinent grounds.